Evaluation of interaction forces between profilin and designed peptide probes by atomic force microscopy - Okada, Tomoko (Langmuir : the ACS journal of surfaces and colloids, 2008)
We evaluated the binding affinity of peptide probes for profilin (protein) using force curve measurement techniques and atomic force microscopy (AFM). The peptide probes designed and synthesized for this investigation were H-A3GP5GP5GP5G-OH (1), H-A3GP5G-OH (2), H-A3G7-OH (3), and H-A3G-OH (4). Each peptide probe was immobilized on a cantilever tip, and the interaction force to profilin, immobilized on a mica substrate, was examined by force curve measurements. The retraction forces obtained showed a sequence-dependent affinity of the peptide probe for profilin. The retraction force for peptide probe 1 was the largest of the four probes examined, and it confirmed that peptide probe 1 has high affinity for profilin. The single molecular retraction force between peptide probe 1 and profilin was estimated to be 96 pN, as determined by Gaussian fitting to the histogram of the retraction forces